Políticas de comercio internacional relacionadas con el clima: Evaluación de los impactos en Bolivia, Colombia, Ecuador y Perú - Aaron Cosbey; Adrien Vogt-Schilb (Inter-American Development Bank (IDB), 2023)
– There is a growing wave of concern for the embodied carbon in traded goods. One manifestation of that concern is large economies such as the USA and the European Union enacting climate-related trade measures, including border carbon adjustment. This paper reviews more than ten climate-related trade measures that are currently enacted or under discussion globally and five initiatives from large companies to source low-carbon inputs. It then assesses Bolivia, Colombia, Ecuador, and Peru's vulnerability to trade restrictions, based on estimated greenhouse gas intensity of their exported goods (using an input-output analysis) relative to other global producers, and an exposure analysis that assesses the likelihood that current importers of these products might implement climate-related trade measures. Finally, it reviews existing scenarios of global oil, natural gas and coal demand, and asks what they mean for fossil fuel exports from these countries. Agricultural goods stand out as vulnerable, as they are the main driver of deforestation and associated emissions. The most serious threat is the vulnerability of fossil fuel exports, primarily crude oil and gas, which dominate the four countries' current exports. The paper exposes recommendations in terms of diversifying the economy away from fossil fuels and preparing exporters to comply with emerging climate-related trade restrictions.
Keywords: F18; Q56; Q54; O13; 330; Trade Policy; Climate Policy; Input-Output Analysis